Adventures in Ring-Contraction Reactions - Silva, Luiz F., Jr. (Synlett, 2014)
Nearly two decades of work on ring-contraction reactions is discussed in this account. We have developed several reliable protocols for the rearrangement of a number of different substrates using thallium(III) salts and, more recently, hypervalent iodine(III) reagents. A variety of ring systems, such as cyclopentanes, cis- and trans-hydrindanes, and indanes, can be obtained using these methods. Additionally, the stereoselective total syntheses of the sesquiterpenes (±)-, (–)- and (+)-mutisianthol and (+)-bakkenolide A, the indole alkaloid (±)- and (+)-trans-trikentrin A, and the potential drug (±)-indatraline have been achieved through a ring-contraction approach.1 Introduction2 Ring-Contraction Reactions Promoted by Thallium(III)2.1 Thallium(III)-Mediated Ring Contraction of Cyclic Ketones2.2 Thallium(III)-Mediated Ring Contraction of Cyclic Olefins2.3 Thallium(III)-Mediated Ring Contraction of Homoallylic Alcohols3 Ring-Contraction Reactions Promoted by Iodine(III)4 Conclusion
Keywords: total synthesis; ring contractions; oxidative rearrangements; thallium(III); hypervalent iodine